It happened on a Sunday - Wolff, Tracy (Entangled: Amara, 2025)
"They call her the Black Widow. A pop star. A tabloid tragedy. A girl who set the world on fire--and got burned in return. But Sloane Walker doesn't care what they say. Not anymore. The headlines, the hashtags, the rumors that never die? Let them come. She's survived worse--like the ex who tried to kill her and the fans who blamed her for surviving. These days, she's armor and eyeliner, singing songs that hurt and pretending they don't. She's halfway through a sold-out tour and dangerously close to unraveling when a meet-and-greet throws her into the path of Mateo Sylvester--a rising star quarterback with a devastating smile and a grandmother who's Sloane's biggest fan. He's got stadiums at his feet and the press eating from his hand. She's got a flask full of sweet tea, a voice full of ghosts, and no patience for golden boys with good intentions. She tells herself it's just a photo op. Just another handshake. Just another charming fan with perfect cheekbones and no idea what it means to bleed for your art. But Mateo sees more than the stage persona. He sees the cracks in her smile. The songs she's too scared to write. The girl underneath the glitter, still fighting to stay. They weren't supposed to fall. Not in the spotlight. Not when the world is watching. And definitely not when the people closest to them would do anything to keep them apart"--provided by publisher.